Pengabdian Masyarakat dalam Upaya Mitigasi Pencemaran Lingkungan Pesisir di Pantai Batu Gong, Sulawesi Tenggara - Tiara, Intan; Karimuna, Siti Rabbani; Apriana, Dhea Resky; Tappo, Liberthy Mendila; Dernayun; Lahata, Astrid Pratiwi; Inggrat, Intan Wahid; Suryaningsi; Pattinasarany, Merlyn Vitaloka; Ardina; Muliani, Sri; Ferniati; Ahmad, Fakhrul Mubarak (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Environmental pollution in coastal areas, particularly due to the accumulation of solid and liquid waste, is an urgent issue globally and in Indonesia. Low public awareness and inadequate waste management facilities exacerbate this condition, as seen at Batu Gong Beach, South Konawe Regency. Previous studies indicate that plastic and organic waste are poorly managed, compounded by a lack of oversight. The objective of this community service activity is to enhance the understanding and awareness of the local community and visitors to Batu Gong Beach regarding plastic waste management and coastal pollution prevention, as well as to foster synergy among stakeholders for a clean, healthy, and sustainable coastal environment. The method used involved a site survey and fieldwork by 12 students from the Faculty of Public Health, Halu Oleo University, on May 29, 2025. The results showed that most of the waste at Batu Gong Beach originated from visitors and sea-borne debris, leading to ecosystem damage and reduced tourist appeal. Collaboration among the government, community, and visitors is crucial to provide waste facilities, conduct regular clean-ups, and raise environmental awareness to ensure the sustainability of Batu Gong Beach.